ANALYSIS OF PRINCIPAL'S LEADERSHIP STYLE, WORK ENVIRONMENT, JOB TRAINING, JOB SATISFACTION ON TEACHER PERFORMANCE AT STATE JUNIOR HIGH SCHOOLS IN EAST MANGGARAI REGENCY WITH WORK MOTIVATION AS AN INTERVENING VARIABLE - Sugiono, Edi; Efendi, Suryono; Jojong, Flavianus Ridwan Jojong (2021)
The purpose of this study was to determine the analysis of the principal's leadership style, work environment, job training, job satisfaction on teacher performance. This research uses quantitative research. The types of data in this study are primary data and secondary data. Data collection techniques used are observation and interview techniques. The population used by the researchers in this study were all public junior high school teachers in East Manggarai Regency who were collected using the purposive sampling method. The data analysis methods in this study are validity testing, reliability testing, hypothesis testing, and Sobel test. Based on the results of the study, the conclusions of this study are as follows: 1) The variables of Leadership Style, Work Environment, Job Satisfaction have a positive and significant effect on work motivation; 2) Job Training variable does not have a positive effect on work motivation; 3) The variables of leadership style, work environment, job satisfaction have a positive and significant effect on performance; 4) Job Training has no positive effect on performance; 5) The variable of work motivation has a significant and significant effect on performance; 6) Variables of Leadership Style, Work Environment, Job Satisfaction have a significant and significant effect on performance; and 7) Job Training has no positive effect on performance.